6-4=7X-9X-8

Simple and best practice solution for 6-4=7X-9X-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-4=7X-9X-8 equation:


Simplifying
6 + -4 = 7X + -9X + -8

Combine like terms: 6 + -4 = 2
2 = 7X + -9X + -8

Reorder the terms:
2 = -8 + 7X + -9X

Combine like terms: 7X + -9X = -2X
2 = -8 + -2X

Solving
2 = -8 + -2X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '2X' to each side of the equation.
2 + 2X = -8 + -2X + 2X

Combine like terms: -2X + 2X = 0
2 + 2X = -8 + 0
2 + 2X = -8

Add '-2' to each side of the equation.
2 + -2 + 2X = -8 + -2

Combine like terms: 2 + -2 = 0
0 + 2X = -8 + -2
2X = -8 + -2

Combine like terms: -8 + -2 = -10
2X = -10

Divide each side by '2'.
X = -5

Simplifying
X = -5

See similar equations:

| 5g+9=-5 | | -2r=-34 | | 1.2(x-5)=1.6(2x+5) | | (x+3)(x+3)=12*x | | (2m+3)(6m-2)= | | 10x+-9x= | | 3r^2-9r-17=2r^2-5-8r | | 44x+7=73 | | 123+45=180 | | -2(8+4h)= | | x=5.6+1.4y | | 123+70=180 | | 2g+5=-3 | | (-7n/12)(9n/14) | | 9-5x=6x | | (2y-3)/(y+3)=5/7 | | 2h+5=3 | | 5x+3=10x+-7 | | 123+75=180 | | (-55)-(-88)= | | 6(7+x)+5x=0 | | -(8-4h)= | | 6f-1=2 | | 4s^4-17s^2+4=0 | | 176+4= | | 5x=7y+28 | | 9+5a=2a+5 | | 2x-1/3x=15 | | (3/8)(8/3)(n) | | (5/16)+(2/3)x=(1/4)-(1/6)x | | (-72)+36= | | (3/8)(8/3) |

Equations solver categories